2020
DOI: 10.1101/2020.04.23.20076877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Detection Using an Isothermal Amplification Reaction and a Rapid, Inexpensive Protocol for Sample Inactivation and Purification

Abstract: As the current SARS-CoV-2 pandemic spreads, the need for more diagnostic capabilities is great. In order to address this need, we have developed a highly sensitive RT-LAMP assay compatible with current reagents, that utilizes a colorimetric readout in as little as 30 minutes. In addition to this, we have developed an inexpensive pipeline to further increase sensitivity without requiring highly specialized equipment. A rapid inactivation protocol capable of inactivating virions, as well as endogenous nucleases,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 11 publications
1
77
0
Order By: Relevance
“…While this clinical validation is focused on nasopharyngeal swabs, which are recommended by the U.S. Centers for Disease Control as the most sensitive specimen type for SARS-CoV-2 detection [11], the same methods can be applied to other sample types as well, possibly including saliva [8]. Oropharyngeal specimens are likely to be compatible given their similar composition to nasopharyngeal specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this clinical validation is focused on nasopharyngeal swabs, which are recommended by the U.S. Centers for Disease Control as the most sensitive specimen type for SARS-CoV-2 detection [11], the same methods can be applied to other sample types as well, possibly including saliva [8]. Oropharyngeal specimens are likely to be compatible given their similar composition to nasopharyngeal specimens.…”
Section: Discussionmentioning
confidence: 99%
“…4A). We used the glass milk protocol developed by Rabe and Cepko [8] to concentrate up to 500 µL of sample into a single RT-LAMP reaction. Purification improved the LoD by ten-fold ( Fig.…”
Section: Assay Performance After Sample Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Proteinase K has the same temperature optimum as the RT-LAMP reaction (65°C) and heat inactivation is not 100% efficient, even when incubating at 95°C for 10 min (see FAQ pages on www.qiagen.com), thus exposing the enzymes in the RT-LAMP reaction to unpredictable proteolytic influences. Rabe and Cepko (2020) suggest to use cheap silika preparation and novel sample inactivation protocols to enrich the RNA prior to LAMP, which however would come at the expense of complicating the simple swab-to-RT-LAMP workflow. Finally, our analysis found that a short heat treatment of 5 min at 95 °C, which poses minimal additional handling steps, does not destroy the RNA but rather stabilised it in the inactivated specimen, and improved the sensitivity and specificity of the swab-to-RT-LAMP assay (Figure 8).…”
Section: Direct and Hot Swab-to-rt-lamp Assaysmentioning
confidence: 99%
“…One promising lead for future applications is the exploration of hot swab-to-RT-LAMP with saliva specimens, which may show a higher sensitivity than in oropharyngeal swab specimens Wyllie et al, 2020). Compatibility of RT-LAMP with direct saliva specimens has been shown before but only using spiked-in IVT RNA (Badhra et al, 2020, Rabe andCepko 2020).…”
Section: Direct and Hot Swab-to-rt-lamp Assaysmentioning
confidence: 99%